Rekonfigurasi Jaringan Pada Penyulang Blahkiuh Dengan Menggunakan Metode Particle Swarm Optimization (PSO) - Putra, Yudha Anggara; Utama, Ngakan Satria; Giriantari, I. A. Dwi (Majalah Ilmiah Teknologi Elektro; Vol 18 No 1 (2019): (Januari - April) Majalah Ilmiah Teknologi Elektro, 2019)
Reconfiguration network is a way to change the switching configuration settings in the network, configuration changes here means closing or opening switches that have a network. This research object is feeder Blahkiuh. Network reconfiguration of feeder Blahkiuh aims to reduce or minimized network power loss. Load flow analysis is done to find the existing network power losses, then optimization using PSO method applied to find the optimum point of intersection which result in reduced power loss in feeder. Research find the optimum power point of intersection is at bus 123, the power loss reduced is 14 kW, from 246 kW to 232 kW.